PENGARUH PENAMBAHAN BERBAGAI DOSIS ZAT PENGATUR TUMBUH NAA (NAPHTALENE ACETIC ACID) PADA PUPUK DAUN TERHADAP SIFAT KIMIA TANAH, PERTUMBUHAN, DAN PRODUKSI TANAMAN CABAI BESAR (Capsicum annum L.) - Futihatu Rizkiani Azizah; Syahrul Kurniawan (Jurnal Tanah dan Sumberdaya Lahan, 2019)
The increase of great chilli concumption may increase great chilli cultivation area in degraded land. To reach high crop production, foliar fertilizer enriched by hormone can be used to improve soil fertility, plant growth and production in great chilli cultivation. This study aimed to determine the effect of addition NAA on soil properties, growth, leaf nutrient content and yield on great chilli. This research took place in Agro Techo Park, Jatikerto Village, Kromengan District, Malang Regency. The study was designed by using a factorial randomized block design with 2 factors that consisted of NAA doses (P1: 0; P2: 75% NAA; P3: 100% NAA; and P4: 125% NAA) and interval application (I1: 14 days and I2: 18 days); each combination treatment was repeated three times. The result showed that difference doses of NAA on foliar fertilizer gave impact on plant growth (i.e height, number of leaf, number of flower per plant, number of fruit per plant) and crop yield of great chilli. Various doses NAA on foliar fertilizer had affected to soil chemical properties (i.e pH, Organic-C, total